Implementation of Green Chemistry in Chemistry Learning: A Literature Review - Rama Cahaya Situngkir; Lera sani Damah Putri; Meilani Azizah; Nurfajriani Nurfajriani (Universitas Negeri Gorontalo, 2026)
This study aims to review and analyze the implementation of green chemistry in chemistry learning through a Systematic Literature Review (SLR), focusing on research trends, methodologies, learning contexts, and forms of application. Green chemistry, introduced by Anastas and Warner, emphasizes the design of efficient, safe, and environmentally friendly chemical processes. Its integration into chemistry education is essential to foster sustainable development and environmental responsibility among students. Data were collected from 100 articles published between 2016 and 2025 in Google Scholar and Publish or Perish, of which 15 articles met the inclusion criteria for further analysis. Narrative synthesis was applied to extract and categorize information regarding research focus, methodology, learning context, and forms of implementation. The results indicate that applying green chemistry principles in chemistry learning strengthens conceptual mastery, motivation, creativity, and ecological awareness. Reported strategies include curriculum integration, eco-friendly laboratory practices, micro-scale experiments, and the development of innovative teaching modules. Despite challenges such as limited resources, teacher readiness, and lack of media, opportunities remain promising when aligned with the Sustainable Development Goals (SDGs). In conclusion, integrating green chemistry into chemistry education enriches learning while supporting the formation of future generations who are more environmentally conscious and committed to sustainability.